Synthesis and characterisation of amorphous MnO2/CNT via solid‐state microwave for high‐performance supercapacitors. (15th February 2020) - Tan, Xiaoqi; Liu, Shuxia; Guo, Qingping; Zhang, Jie; Liang, Shujun; He, Maoyong; Luo, Jujie
Summary: Amorphous MnO2 was attached to carbon nanotubes (CNTs) in 60 seconds by solid‐state microwave method. As electrodes in supercapacitors, the coactions of the MnO2 and CNT augmented the actual value of capacitance to 1250 F g −1, and cycle steadiness held 80% of the starting value after 7000 cycles. The equipped MnO2 /CNT//AC asymmetric supercapacitor (ASC) manifested preferable energy density with 33.5 Wh kg −1 (at 400 W kg −1 ). Its glorious electrochemical properties of MnO2 /CNT demonstrated that the microwave method has great potency to realise the composite of electrode materials. Abstract : Amorphous MnO2 /CNT was synthesised by solid‐state microwave method. The synergy between CNT and MnO2 promotes the electrochemical properties of the electrode. The assembled MnO2 /CNT//AC ASC has great application potential.